Histomorphometric examination of long-term changes in temporomandibular joints after mandibular lengthening by distraction osteogenesis in rabbits - Mihmanli, Ahmet; Dolanmaz, DOĞAN; DOLANMAZ, DOĞAN; Tuz, Hakan; Pampu, Alper; Donmez, Hasan Huseyin (My University, 2012)
Objective. The purpose of this study was to evaluate long-term histomorphometric changes in temporomandibular joints (TMJs) of rabbits after mandibular distraction osteogenesis (DO).